An injection-molded heterogeneous joint based on metal ion coordination and a preparation method thereof

In the preparation process of injection molded metal-polymer joints, the micro-nano-scale surface structure is constructed and coordination bonds are formed using metal ion coordination methods, which solves the problem of insufficient bonding strength of existing joints and realizes high-strength metal-polymer joints.

CN118082096BActive Publication Date: 2025-02-28SHANDONG UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410163062.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-02-05
Publication Date
2025-02-28
Estimated Expiration
2044-02-05

AI Technical Summary

Technical Problem

The existing injection molded metal-polymer joints have insufficient bonding strength, making it difficult to meet the needs of high-performance insulators.

Method used

Using a preparation method based on metal ion coordination, the metal insert is placed in a water solution of strong oxidizing metal ion salt and hydrazine for ultrasonic vibration treatment, and a micro-nanoscale cross-scale surface microstructure is constructed, and impregnated in the ethanol solution of transition metal ion salt to form coordination bonds to achieve chemical bonds of metal-polymers.

Benefits of technology

The tensile shear strength of injection molded heterogeneous joints is significantly improved, reaching 55-60MPa, which is much higher than the strength of existing injection molded joints.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of heterogeneous metal / polymer interface bonding, and in particular to an injection-molded heterogeneous joint based on metal ion coordination and a preparation method thereof, comprising the following steps: placing a metal insert to be treated in a strongly oxidizing metal ion salt aqueous solution, and subjecting it to ultrasonic vibration treatment, and subjecting the metal surface to preliminary chemical corrosion; placing the metal insert after preliminary chemical corrosion in an aqueous solution of hydrazine, and subjecting it to ultrasonic vibration treatment, and subjecting the metal surface to secondary chemical corrosion; placing the metal insert after secondary chemical corrosion in an ethanol solution of a transition metal ion salt, and subjecting the metal surface to immersion treatment; placing the metal insert after immersion treatment in a mold cavity, closing the mold to injection-mold the polymer, and after baking treatment, obtaining an injection-molded heterogeneous joint. The preparation method of the present invention can increase the strength of the metal-polymer joint obtained by injection molding to 55-60MPa under the dual effects of mechanical interlocking and coordination bonding, which is much higher than the existing injection-molded joint strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of dissimilar metal / polymer interface bonding, in particular to an injection-molded heterogeneous joint based on metal ion coordination and a preparation method thereof. Background Art

[0002] Based on the requirements of environmental protection and sustainable development, thermoplastic polymers such as PET, PBT and PPS have attracted more and more attention in the field of electrical insulation due to their excellent insulation, specific strength and thermoplasticity. Usually electrical insulation parts are composed of insulating engineering plastics and metal inserts. The interface bonding between the central conductor (metal) and the insulating part (polymer) is particularly important for the insulation performance, anti-puncture performance and pressure resistance of the insulation part.

[0003] In order to improve the metal / polymer interface bonding strength, researchers have conducted a series of studies on interface bonding using processes such as mechanical connection, adhesive bonding, hot pressing connection, stir friction welding, and laser welding. The metal / polymer bonding strength is also improved through methods such as metal surface pretreatment, polymer modification, and inserting an intermediate layer.

[0004] However, in the metal-polymer bonding process, mechanical connection joints are prone to stress concentration and have a short service life; adhesive bonding joints have poor water absorption and are prone to environmental pollution; hot pressing connection processes have problems such as long bonding time and serious energy waste; various types of welded joints have poor dimensional stability and polymers are prone to burning. Injection molding has the advantages of high molding efficiency, diversified product shapes, and extremely high energy utilization, but in actual production processes, the metal-polymer interface bonding strength is much lower than the process described above. Therefore, how to enhance the bonding strength of injection molded metal-polymer joints has become a technical problem for researchers in this field.

[0005] In order to improve the strength of injection molded metal-polymer joints, researchers have carried out a series of research methods, which can be summarized as two methods: metal surface morphology treatment and metal-polymer interface modification. Among them, metal surface morphology treatment can improve the roughness of the metal surface and realize metal-polymer mechanical linkage, mainly including metal surface sandblasting, micro-nanosecond laser etching, chemical corrosion, anodizing and micro-arc oxidation. Metal-polymer interface modification, by inserting intermediate active bodies, realizes the chemical bonding of metal-polymer, mainly including coating active chemical reagents, chemical vapor deposition, plasma treatment, hot water bath, etc. The combined pretreatment of the above methods can achieve a significant improvement in the bonding strength of metal-polymer joints, but none of them have exceeded 40MPa.

[0006] In view of this, the present invention is proposed. Summary of the invention

[0007] The purpose of the present invention is to provide a method for preparing an injection molded heterogeneous joint based on metal ion coordination. The injection molded heterogeneous joint prepared by this method has a tensile shear strength of 55-60MPa, which is much higher than the strength of existing metal-polymer injection molded joints.

[0008] In a first aspect, the present invention provides a method for preparing an injection molded heterogeneous joint based on metal ion coordination, comprising the following steps:

[0009] S1. placing the metal insert to be treated in a strong oxidizing metal ion salt solution and subjecting it to ultrasonic vibration treatment to perform preliminary chemical corrosion on the metal surface;

[0010] S2, placing the metal insert after the initial chemical corrosion in an aqueous solution of hydrazine and subjecting it to ultrasonic vibration treatment to perform secondary chemical corrosion on the metal surface;

[0011] S3, placing the metal insert after the secondary chemical corrosion in a transition metal ion salt ethanol solution to perform an immersion treatment on the metal surface;

[0012] S4, placing the impregnated metal insert in the mold cavity, closing the mold to injection-mold the polymer, and after baking, obtaining an injection-molded heterogeneous joint.

[0013] In order to improve the bonding strength of injection molded heterogeneous joints, the present invention firstly places the metal insert to be treated in a strong oxidizing metal ion salt aqueous solution and a hydrazine aqueous solution in sequence, and simultaneously performs ultrasonic vibration treatment, so as to construct a micro-nanoscale cross-scale surface microstructure on the metal surface, thereby significantly enhancing the super-strong mechanical linkage effect of the metal surface during the injection molding process; then, the metal insert after secondary chemical corrosion is placed in a transition metal ion salt ethanol solution, and the metal surface is immersed in treatment, which, on the one hand, can not only convert the hydrophobic metal surface into a hydrophilic metal surface, but also realize the transformation of the wettability of the metal surface, thereby making it easier for the polymer to be filled into the micro-nanoscale cross-scale surface structure, and realize the full combination of metal and polymer; on the other hand, the transition metal ions solidified after immersion and the metal surface oxide layer and the adsorbed O 2- Coordination bonds can be generated to achieve chemical bonding between transition metal ions and the surface of metal inserts. After injection molding, the metal-polymer joint is heat treated to make the transition metal ions generate coordination bonds with elements such as -O- and =O in the polymer, thereby achieving chemical bonding between metal and polymer.

[0014] Studies have shown that the preparation method of the present invention can increase the strength of the metal-polymer joint obtained by injection molding to 55-60MPa under the dual effects of mechanical anchoring and coordination bonding, which is much higher than the strength of existing injection molded joints.

[0015] As a preferred embodiment of the present technical solution, in step S1, the strong oxidizing metal ion salt specifically includes any one or more of FeCl3, CuCl2, NaMnO4 and Na2CrO4, and the concentration of the strong oxidizing metal ion salt aqueous solution is 10-20wt.%, and the concentration can be selected according to the oxidizing property of the metal ion salt solution. For low-oxidizing metal ion salts, a solution with a slightly higher concentration can be selected, and for high-oxidizing metal ion salts, a solution with a lower concentration can be selected; and the final use concentration needs to be determined according to the metal surface area to ensure that the metal corrosion surface morphology is not affected by the reduction in metal ion concentration.

[0016] Specifically, in step S1, during the initial chemical etching, the temperature is controlled to be 40-50° C. and the time is 10-20 minutes.

[0017] At this temperature, ultrasonic vibration treatment of the metal surface can not only increase the rate of generation of micro-nanoscale structures on the metal surface, but also ensure the uniformity of the micro-nanoscale structures on the metal surface. It can not only enhance the super-strong mechanical linkage effect of metal-polymer, but also provide a physical basis for the immersion treatment of the metal surface.

[0018] As a preferred technical solution, in step S2, the concentration of hydrazine in the hydrazine aqueous solution is 1-5wt.%. In the present invention, after the metal surface is treated with a strong oxidizing metal ion salt aqueous solution, a secondary chemical corrosion treatment with a hydrazine aqueous solution is performed. The pit structure obtained by hydrazine corrosion of the metal surface is more conducive to the adhesion of transition metal ion salts.

[0019] Preferably, during the secondary chemical etching, the temperature is controlled to be 30-40° C. and the time is 1-5 min.

[0020] As a preferred embodiment of the present technical solution, in step S3, the transition metal ion salt specifically includes any one or more of ZrCl4, CeCl3 and Sc(NO3)3, and the concentration of the transition metal ion salt ethanol solution is preferably 0.5-2wt.%;

[0021] Preferably, during the immersion treatment, the temperature is controlled at 20-30°C and the time is 80-100 minutes.

[0022] Under the impregnation conditions of the present invention, transition metal ions can be stably bound to the metal surface, which can not only convert the hydrophobic metal surface into a hydrophilic metal surface, realize the transformation of the wettability of the metal surface, thereby making it easier for the polymer to be filled into the micro-nanoscale cross-scale surface structure, realize the full combination of metal and polymer, but also the transition metal ions can be bound to the metal surface oxide layer and the adsorbed O 2-A coordination bond can be generated to achieve chemical bonding between the transition metal ions and the surface of the metal insert. After injection molding, heat treatment of the injection molded heterogeneous joint can generate coordination bonds between the transition metal ions and elements such as -O- and =O in the polymer. Therefore, the treatment method of the transition metal ions of the present invention can significantly improve the chemical bonding force between the metal and the polymer.

[0023] As a preferred embodiment of the present technical solution, after the primary chemical corrosion and the secondary chemical corrosion, the metal insert needs to be ultrasonically cleaned with anhydrous ethanol to remove the strong oxidizing metal ion salt solution and hydrazine solution remaining on the metal surface, and the surface is dried with a nitrogen gun;

[0024] Preferably, the ultrasonic cleaning is performed 2-3 times, and the duration of each ultrasonic cleaning is 10-20 minutes;

[0025] Preferably, during the ultrasonic cleaning, the working power of the ultrasonic cleaning machine is controlled to be 50-70W and the frequency to be 30-50KHz.

[0026] As a preferred embodiment of the present technical solution, in step S3, the impregnated metal insert is placed in an oven and baked at 70-120°C for 30-60 minutes to allow the transition metal ions to react with the metal surface oxide layer and the adsorbed O 2- It can generate coordination bonds to achieve chemical bonding between transition metal ions and the surface of metal inserts, thereby completing the impregnation treatment of the metal surface;

[0027] Preferably, before baking, the metal insert is rinsed with anhydrous ethanol and the surface is dried with a nitrogen gun to remove the transition metal ion salt solution remaining on the metal surface.

[0028] As a preferred embodiment of the present technical solution, in step S4, the impregnated metal insert is placed in the mold cavity, the mold is closed and the polymer is injection-molded, and the metal insert is baked to form coordination bonds between the transition metal ions and elements such as -O- and =O in the polymer. Specifically, during the baking treatment, the temperature is preferably 70-120°C and the time is preferably 2-4h.

[0029] As a preferred embodiment of the present technical solution, in steps S1 and S2, during the ultrasonic vibration, the working power of the ultrasonic vibration machine is controlled to be 80-100W and the frequency to be 30-50KHz.

[0030] In the second aspect, the present invention also discloses an injection molded heterogeneous joint based on metal ion coordination prepared by the above method, which should also belong to the protection scope of the present invention. Specifically, the tensile shear strength of the injection molded heterogeneous joint is 55-60MPa.

[0031] The preparation method of the injection molded heterogeneous joint based on the metal ion coordination of the present invention has at least the following technical effects:

[0032] In the preparation method of the injection-molded heterogeneous joint based on the coordination effect of metal ions of the present invention, first, the metal insert to be treated is placed in a strong oxidizing metal ion salt aqueous solution and a hydrazine aqueous solution in sequence, and ultrasonic vibration treatment is performed at the same time, so that a micro-nanoscale cross-scale surface microstructure can be constructed on the metal surface, thereby significantly enhancing the mechanical linkage effect of the metal surface during the injection molding process; then, the metal insert after secondary chemical corrosion is placed in a transition metal ion salt ethanol solution, and the metal surface is immersed in treatment to solidify the transition metal ions on the metal surface. On the one hand, not only the hydrophobic metal surface can be converted into a hydrophilic metal surface, and the wettability of the metal surface can be changed, so that the polymer can be more easily filled into the micro-nanoscale cross-scale surface structure, and the full combination of metal and polymer can be achieved. On the other hand, the transition metal ions solidified after immersion are bound to the metal surface oxide layer and the adsorbed O 2- A coordination bond can be generated to achieve chemical bonding between the transition metal ions and the surface of the metal insert. After injection molding, the injection molded heterogeneous joint is heat treated to generate coordination bonds between the transition metal ions and elements such as -O- and =O in the polymer, thereby achieving chemical bonding between the metal and the polymer. Therefore, the preparation method of the present invention can increase the strength of the metal-polymer joint obtained by injection molding to 55-60MPa under the dual effects of mechanical anchoring and coordination chemistry, which is much higher than the strength of the existing injection molded joints. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0034] Figure 1 The flowchart of the preparation method of the injection molded heterogeneous joint based on the coordination effect of metal ions of the present invention;

[0035] Figure 2 The surface SEM electron microscope images of the aluminum alloy inserts obtained in Comparative Examples 1-4 of the present invention;

[0036] Figure 3 The contact angle statistics of deionized water droplets on the surface of aluminum alloy inserts obtained in Comparative Examples 1-4 of the present invention;

[0037] Figure 4 The XPS principle diagram of the coordination bonding between the transition metal ions on the surface of the aluminum alloy insert obtained in Comparative Examples 1-4 of the present invention and the oxide layer on the metal surface (taking ZrCl4 as an example);

[0038] Figure 5FTIR and XPS principle diagram of coordination bonding between transition metal ions and polymers (taking ZrCl4 as an example), (a) is the FTIR total spectrum, (bd) are the functional group peak magnifications, and (e) is the uncoated Zr 4+ Combined with the O1s peak spectrum of the interface polymer surface, (f) is the Zr coated 4+ And heat treatment combined with the interface polymer surface O1s peak spectrum;

[0039] Figure 6 This is a comparison chart of the strength of each injection molded joint;

[0040] Figure 7 This is a comparison chart of the concentration intensity of different transition metal cations in the present invention (taking ZrCl4 as an example). DETAILED DESCRIPTION

[0041] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.

[0042] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present application. As used herein, unless the context clearly indicates otherwise, the singular form also includes the plural form. In addition, it should be understood that when the terms "comprise" and / or "include" are used in this description, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.

[0043] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0044] Example 1

[0045] S11, placing the metal insert to be treated in a 15wt.% FeCl3 aqueous solution, and treating it at 45°C for 15 minutes under the vibration of an ultrasonic vibrator with a working power of 90W and a frequency of 40KHz to perform preliminary chemical corrosion on the metal surface;

[0046] After preliminary chemical corrosion of the metal surface, the metal insert is immersed in anhydrous ethanol and ultrasonically cleaned for 15 minutes. The cleaning is repeated 2-3 times, and then taken out and dried with a nitrogen gun. During ultrasonic cleaning, the working power of the ultrasonic cleaning machine is 60W and the frequency is 40KHz.

[0047] S12, first, hydrazine is dissolved in deionized water to prepare a 3wt.% N2H4 solution, the metal insert after the preliminary chemical corrosion is placed in the N2H4 aqueous solution, and treated at 35°C for 3 minutes under the vibration of an ultrasonic vibration machine with a working power of 90W and a frequency of 40KHz, so as to perform secondary chemical corrosion on the metal surface;

[0048] After secondary chemical corrosion of the metal surface, the metal insert is immersed in anhydrous ethanol and ultrasonically cleaned for 15 minutes. The cleaning is repeated 2-3 times, and then taken out and dried with a nitrogen gun. During ultrasonic cleaning, the working power of the ultrasonic cleaning machine is 60W and the frequency is 40KHz.

[0049] S13, dissolving ZrCl4 in anhydrous ethanol, and ultrasonically vibrating at 45°C for 60 minutes to prepare a 1.5wt.% transition metal ion salt solution, placing the metal insert after secondary chemical corrosion in the transition metal ion salt ethanol solution, and performing an immersion treatment on the metal surface, placing the impregnated metal insert in an oven, and baking at 100°C for 40 minutes to complete the immersion treatment of the metal surface;

[0050] S14. Rinse the metal insert with anhydrous ethanol and dry the surface with a nitrogen gun, then place the metal insert in the mold cavity, close the mold, injection-mold the polymer, and bake at 100° C. for 3 hours to obtain an injection-molded heterogeneous joint.

[0051] Example 2

[0052] S21, placing the metal insert to be treated in a 15wt.% CuCl2 aqueous solution, and treating it at 40°C for 20 minutes under the vibration of an ultrasonic vibrator with a working power of 90W and a frequency of 40KHz, to perform preliminary chemical corrosion on the metal surface;

[0053] After preliminary chemical corrosion of the metal surface, the metal insert is immersed in anhydrous ethanol and ultrasonically cleaned for 15 minutes. The cleaning is repeated 2-3 times, and then taken out and dried with a nitrogen gun. During ultrasonic cleaning, the working power of the ultrasonic cleaning machine is 60W and the frequency is 40KHz.

[0054] S22. First, hydrazine is dissolved in deionized water to prepare a 5 wt.% N2H4 solution, and the metal insert after the preliminary chemical corrosion is placed in the N2H4 aqueous solution, and treated at 35° C. for 3 minutes under the vibration of an ultrasonic vibration machine with a working power of 90 W and a frequency of 40 KHz to perform secondary chemical corrosion on the metal surface;

[0055] After secondary chemical corrosion of the metal surface, the metal insert is immersed in anhydrous ethanol and ultrasonically cleaned for 15 minutes. The cleaning is repeated 2-3 times, and then taken out and dried with a nitrogen gun. During ultrasonic cleaning, the working power of the ultrasonic cleaning machine is 60W and the frequency is 40KHz.

[0056] S23, dissolving CeCl3 in anhydrous ethanol, and ultrasonically vibrating at 50°C for 50 minutes to prepare a 1.5wt.% transition metal ion salt solution, placing the metal insert after secondary chemical corrosion in the transition metal ion salt ethanol solution, and performing an immersion treatment on the metal surface, placing the impregnated metal insert in an oven, and baking at 100°C for 50 minutes to complete the immersion treatment of the metal surface;

[0057] S24. Rinse the metal insert with anhydrous ethanol and dry the surface with a nitrogen gun, then place the metal insert in the mold cavity, close the mold, injection-mold the polymer, and bake at 100° C. for 4 hours to obtain an injection-molded heterogeneous joint.

[0058] Example 3

[0059] S31, placing the metal insert to be treated in a 20wt.% NaMnO4 aqueous solution, and treating it at 40°C for 20 minutes under the vibration of an ultrasonic vibrator with a working power of 9W and a frequency of 40KHz, to perform preliminary chemical corrosion on the metal surface;

[0060] After preliminary chemical corrosion of the metal surface, the metal insert is immersed in anhydrous ethanol and ultrasonically cleaned for 15 minutes. The cleaning is repeated 2-3 times, and then taken out and dried with a nitrogen gun. During ultrasonic cleaning, the working power of the ultrasonic cleaning machine is 60W and the frequency is 40KHz.

[0061] S32, first, hydrazine is dissolved in deionized water to prepare a 5wt.% N2H4 solution, the metal insert after the preliminary chemical corrosion is placed in the N2H4 aqueous solution, and treated at 30°C for 5 minutes under the vibration of an ultrasonic vibration machine with a working power of 90W and a frequency of 40KHz, so as to perform secondary chemical corrosion on the metal surface;

[0062] After secondary chemical corrosion of the metal surface, the metal insert is immersed in anhydrous ethanol and ultrasonically cleaned for 15 minutes. The cleaning is repeated 2-3 times, and then taken out and dried with a nitrogen gun. During ultrasonic cleaning, the working power of the ultrasonic cleaning machine is 60W and the frequency is 40KHz.

[0063] S33, dissolving Sc(NO3)3 in anhydrous ethanol, and subjecting the mixture to ultrasonic vibration for 40 minutes at a temperature of 50°C to prepare a 1.5wt.% transition metal ion salt solution, placing the metal insert after secondary chemical corrosion in the transition metal ion salt ethanol solution, and performing an immersion treatment on the metal surface, placing the impregnated metal insert in an oven, and baking it at 120°C for 50 minutes to complete the immersion treatment of the metal surface;

[0064] S34. Rinse the metal insert with anhydrous ethanol and dry the surface with a nitrogen gun, then place the metal insert in the mold cavity, close the mold, injection-mold the polymer, and bake at 120° C. for 3 hours to obtain an injection-molded heterogeneous joint.

[0065] Example 4

[0066] S41, placing the metal insert to be treated in a 10wt.% Na2CrO4 aqueous solution, and treating it at 40°C for 20 minutes under the vibration of an ultrasonic vibrator with a working power of 90W and a frequency of 40KHz, to perform preliminary chemical corrosion on the metal surface;

[0067] After preliminary chemical corrosion of the metal surface, the metal insert is immersed in anhydrous ethanol and ultrasonically cleaned for 15 minutes. The cleaning is repeated 2-3 times, and then taken out and dried with a nitrogen gun. During ultrasonic cleaning, the working power of the ultrasonic cleaning machine is 60W and the frequency is 40KHz.

[0068] S42, first, dissolving hydrazine in deionized water to prepare a 1wt.% N2H4 solution, placing the metal insert after preliminary chemical corrosion in the N2H4 aqueous solution, and treating it at 30°C for 5 minutes under the vibration of an ultrasonic vibration machine with a working power of 90W and a frequency of 40KHz, so as to perform secondary chemical corrosion on the metal surface;

[0069] After secondary chemical corrosion of the metal surface, the metal insert is immersed in anhydrous ethanol and ultrasonically cleaned for 15 minutes. The cleaning is repeated 2-3 times, and then taken out and dried with a nitrogen gun. During ultrasonic cleaning, the working power of the ultrasonic cleaning machine is 50-70W and the frequency is 30-50KHz.

[0070] S43, dissolving ZrCl4 in anhydrous ethanol at 45°C and ultrasonically vibrating for 80 minutes to prepare a 1.5wt.% transition metal ion salt solution, placing the metal insert after secondary chemical corrosion in the transition metal ion salt ethanol solution, performing an immersion treatment on the metal surface, placing the impregnated metal insert in an oven, and baking at 100°C for 50 minutes to complete the immersion treatment of the metal surface;

[0071] S44. Rinse the metal insert with anhydrous ethanol and dry the surface with a nitrogen gun, then place the metal insert in the mold cavity, close the mold, injection-mold the polymer, and bake at 100° C. for 3 hours to obtain an injection-molded heterogeneous joint.

[0072] Comparative Example 1 (Sandpaper Polishing)

[0073] The aluminum alloy insert is polished with sandpaper, placed in a mold cavity, and the mold is closed and a polymer is injection-molded to obtain a metal-polymer joint.

[0074] Comparative Example 2 (Ultrasonic FeCl3 Corrosion)

[0075] The aluminum alloy insert to be treated is placed in a 15wt.% FeCl3 aqueous solution, and treated at 45°C for 15 minutes under the vibration of an ultrasonic vibrator with a working power of 90W and a frequency of 40KHz, so as to only perform preliminary chemical corrosion on the metal surface;

[0076] The aluminum alloy insert after preliminary chemical etching is cleaned, and then the aluminum alloy insert is placed in a mold cavity, and the mold is closed and polymer is injection-molded to obtain a metal-polymer joint;

[0077] The other steps and parameters are basically the same as those in Example 1.

[0078] Comparative Example 3 (Ultrasonic Hydrazine Corrosion)

[0079] The aluminum alloy insert to be treated is placed in a 3wt.% hydrazine solution and treated at 35°C for 3 minutes under the vibration of an ultrasonic vibrator with a working power of 90W and a frequency of 40KHz, so that only the metal surface is chemically corroded;

[0080] The aluminum alloy insert after chemical corrosion is cleaned, and then the aluminum alloy insert is placed in a mold cavity, and the mold is closed and a polymer is injected to obtain a metal-polymer joint;

[0081] The other steps and parameters are basically the same as those in Example 1.

[0082] Comparative Example 4 (Ultrasonic FeCl3+Hydrazine Corrosion)

[0083] The aluminum alloy insert to be treated is placed in a 15wt.% FeCl3 aqueous solution, and treated at 45°C for 15 minutes under the vibration of an ultrasonic vibrator with a working power of 90W and a frequency of 40KHz, so as to only perform preliminary chemical corrosion on the metal surface;

[0084] The aluminum alloy insert after the preliminary chemical etching was cleaned, and then placed in a 3wt.% hydrazine solution, and treated at 25°C for 3 minutes under the vibration of an ultrasonic vibrator with a working power of 90W and a frequency of 40KHz, to perform secondary chemical etching on the metal surface;

[0085] The aluminum alloy insert after the secondary chemical corrosion is cleaned, and then the aluminum alloy insert is placed in a mold cavity, and the mold is closed and a polymer is injection-molded to obtain a metal-polymer joint.

[0086] Comparative Example 5

[0087] The metal insert is placed in the mold cavity, and after the mold is closed and the polymer is injected, no baking treatment is performed;

[0088] The other steps and parameters are basically the same as those in Example 1.

[0089] Comparative Example 6

[0090] NaOH was used to replace the 15 wt.% FeCl3 aqueous solution in Example 1.

[0091] The other steps and parameters are basically the same as those in Example 1.

[0092] Comparative Example 7

[0093] Use H2O2 to replace the N2H4 aqueous solution in Example 1,

[0094] The other steps and parameters are basically the same as those in Example 1.

[0095] Comparative Example 8

[0096] Reversing the order of treating the metal insert with FeCl3 aqueous solution and N2H4 aqueous solution;

[0097] The other steps and parameters are basically the same as those in Example 1.

[0098] Comparative Example 9

[0099] Sodium dodecylbenzene sulfonate is used to replace the transition metal ion salt solution in Example 1 to perform an immersion treatment on the metal insert;

[0100] The other steps and parameters are basically the same as those in Example 1.

[0101] First, the present invention uses the microscopic morphology, wettability and surface energy of the aluminum alloy insert surface under different treatment conditions of comparative examples 1-4 to study the results. Figure 2-4 shown.

[0102] Depend on Figure 2 It can be seen that after the preliminary ultrasonic vibration corrosion treatment with a strong oxidizing metal ion salt solution and the secondary chemical ultrasonic vibration corrosion treatment with a hydrazine solution, a micro-nanoscale cross-scale structure can be produced on the surface of the aluminum alloy insert, which can play a role of super strong mechanical anchoring during the injection molding process.

[0103] Depend on Figure 3It can be seen that after the transition metal ions are solidified on the metal surface, the wettability of the metal surface can be transformed, converting the hydrophobic surface into a hydrophilic surface, making it easier for the polymer to be filled into the micro-nanoscale cross-scale surface structure, thereby achieving full metal-polymer bonding.

[0104] Depend on Figure 4 It can be seen that the solidified transition metal ions after impregnation are bound to the metal surface oxide layer and the adsorbed O 2- Coordination bonds can be generated to achieve chemical bonding between transition metal ions and the surface of metal inserts. Heat treatment of the metal-polymer joint after injection molding can also cause transition metal ions to generate coordination bonds with elements such as -O- and =O in the polymer, thereby achieving chemical bonding between metal and polymer.

[0105] Depend on Figure 5 It can be seen that heat treatment of the metal-polymer joint after injection molding can further produce coordination bonds between the transition metal ions and functional groups such as -O- and =O in the polymer, thereby realizing the chemical bonding of the metal-polymer. Therefore, heat treatment of the injection-molded heterogeneous joint after injection molding can significantly improve the tensile shear strength of the injection-molded heterogeneous joint.

[0106] The present invention further studies the influence of different injection molding conditions on the tensile shear strength of injection molded heterogeneous joints. Figure 6 shown.

[0107] The present invention also tests the effect of different transition metal ion salt solution concentrations on the tensile shear strength of injection molded heterogeneous joints. The test results are as follows: Figure 7 shown.

[0108] Depend on Figure 7 It can be seen that when the concentration of the transition metal ion salt ethanol solution is 1.5 wt.%, the highest tensile shear strength can be obtained.

[0109] In order to further study the effect of the treatment method of the present invention on the tensile shear strength of injection molded heterogeneous joints, the present invention measured the tensile shear strength of the injection molded heterogeneous joints obtained in Examples 1-4 and Comparative Examples 1-9. The test results are shown in Table 1.

[0110] Table 1 Tensile shear strength test results

[0111]

[0112]

[0113] As can be seen from Table 1, the method of treating the metal surface by successively using a strong oxidizing metal ion salt solution, a hydrazine solution and a transition metal salt solution can significantly improve the metal-polymer interface bonding strength, and its tensile shear strength can reach 55-60MPa, which is much higher than the strength of the existing injection molded heterogeneous joints.

[0114] Control Example 5 was not subjected to baking treatment. Although the strength of the obtained injection-molded heterogeneous joint was improved to a certain extent, its tensile shear strength still needed to be improved compared with Example 1. This may be because the transition metal cations failed to produce sufficient chemical coordination bonding with -O- and =O in the plastic, and the mechanical linkage effect of the metal-polymer interface was poor.

[0115] In Control Example 6, NaOH was used to replace the strongly oxidizing metal ion salt solution in Example 1. Although the strength of the obtained injection-molded heterogeneous joint was improved to a certain extent, its tensile shear strength still needed to be improved compared with Example 1. This may be because a cross-scale structure could not be constructed on the metal surface, and the mechanical linkage effect of the metal-polymer interface was poor.

[0116] Comparative Example 7 uses H2O2 to replace the aqueous solution of hydrazine in Example 1. The strength of the obtained metal-polymer injection molded joint is relatively poor compared with Example 1. The reason may be that only micron-scale structures are generated on the surface, and nano-scale pit structures cannot be generated on the metal surface, and the adhesion effect of transition metal cations is extremely poor. The weak mechanical linkage and extremely poor coordination bonding cannot further improve the interface bonding strength.

[0117] The control example 8 reverses the treatment order of the strong oxidizing metal ion salt solution and the hydrazine solution on the metal insert. The reason why the strength of the obtained metal-polymer injection molded joint is relatively poor compared with that of Example 1 may be that the extremely strong oxidizing corrosion effect of the strong oxidizing metal ion salt destroys the nano-scale pit structure obtained by corrosion of the hydrazine solution, affecting the adhesion of the transition metal ions, thereby reducing the coordination bonding effect of the transition metal ions.

[0118] In Control Example 9, sodium dodecylbenzene sulfonate was used to replace the transition metal ion salt solution in Example 1 to impregnate the metal insert. The strength of the resulting metal-polymer injection molded joint was relatively poor compared with that in Example 1. The reason may be that sodium dodecylbenzene sulfonate failed to produce chemical bonding with the metal and the polymer, and only had a cross-scale mechanical linkage effect, and could not produce super-strong interface bonding.

[0119] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing an injection molded heterogeneous joint based on metal ion coordination, characterized in that: The following steps are involved: S1. placing the metal insert to be treated in a strong oxidizing metal ion salt solution and subjecting it to ultrasonic vibration treatment to perform preliminary chemical corrosion on the metal surface; S2, placing the metal insert after the initial chemical corrosion in an aqueous solution of hydrazine and subjecting it to ultrasonic vibration treatment to perform secondary chemical corrosion on the metal surface; S3, placing the metal insert after the secondary chemical corrosion in a transition metal ion salt ethanol solution to perform an immersion treatment on the metal surface; S4, placing the impregnated metal insert in a mold cavity, closing the mold to inject the polymer, and baking to obtain an injection-molded heterogeneous joint; The metal insert is made of aluminum alloy; The transition metal ion salt includes any one or more of CeCl3, ZrCl4 and Sc(NO3)3, and the concentration of the transition metal ion salt ethanol solution is 0.5-2wt.%; During the immersion treatment, the temperature is controlled at 20-30°C and the time is 80-100 minutes; In step S1, the strong oxidizing metal ion salt includes any one or more of FeCl3, CuCl2, NaMnO4 and Na2CrO4, and the concentration of the strong oxidizing metal ion salt aqueous solution is 10-20wt.%; In step S1, during the initial chemical etching, the temperature is controlled to be 40-50°C and the time is 10-20 minutes.

2. The preparation method according to claim 1, characterized in that: In step S2, the concentration of hydrazine in the aqueous solution of hydrazine is 1-5wt.%; During the secondary chemical etching, the temperature is controlled at 30-40° C. and the time is 1-5 min.

3. The preparation method according to claim 1, characterized in that: After the initial chemical corrosion and the secondary chemical corrosion, the metal inserts need to be ultrasonically cleaned with anhydrous ethanol and the surface is dried with a nitrogen gun; The ultrasonic cleaning is performed 2-3 times, and the duration of each ultrasonic cleaning is 10-20 minutes; During the ultrasonic cleaning, the working power of the ultrasonic cleaning machine is controlled to be 50-70W and the frequency to be 30-50KHz.

4. The preparation method according to claim 1, characterized in that: In step S3, the impregnated metal insert is placed in an oven and baked at 70-120° C. for 30-60 min to complete the impregnation treatment of the metal surface; Before baking, the metal inserts need to be rinsed with anhydrous ethanol and the surface dried with a nitrogen gun.

5. The preparation method according to claim 1, characterized in that: In step S4, during the baking process, the temperature is controlled to be 70-120° C. and the time is 2-4 hours.

6. The preparation method according to claim 1, characterized in that: In steps S1 and S2, during the ultrasonic vibration, the working power of the ultrasonic vibration machine is controlled to be 80-100W and the frequency to be 30-50KHz.

Citation Information

Patent Citations

  • Preparation method of aluminum alloy resin composite and aluminum alloy resin composite

    CN103290450A

  • Method for modifying interface of fiber metal laminated plate through physical-chemical synergism and application

    CN117299511A